Adipocytes do not significantly contribute to plasma angiotensinogen. (October 2016) - Koizumi, Masahiro; Niimura, Fumio; Fukagawa, Masafumi; Matsusaka, Taiji
Recently, it has been reported that 25% of plasma angiotensinogen (Agt) is derived from fat. Meanwhile, liver-specific Agt knockout (KO) mice have markedly low plasma Agt, which may be due to reduced fat mass. To study the contribution of the fat to plasma Agt, we tested whether increasing fat mass can elevate plasma Agt and blood pressure in liver- Agt KO mice. Epididymal fat mass in liver- Agt KO mice fed a high-fat diet (HFD) was 4.1-fold larger than that in liver- Agt KO mice on a normal-fat diet (NFD). The liver- Agt KO mice on NFD were hypotensive with low levels of plasma Agt (on average, 0.11 vs 2.38 μg/ml). HFD slightly increased plasma Agt (0.17 μg/ml) without increase in blood pressure. To further increase fat mass, liver- Agt KO mice were fed HFD and simultaneously supplemented with low-dose angiotensin II and compared with control mice. Fat mass was comparable between the two groups. However, liver- Agt KO mice had uniformly low plasma Agt (0.09 vs 2.07 μg/ml) and systolic blood pressure (78±12 vs 111±6 mm Hg). In conclusion, adipocyte-derived Agt has essentially no contribution to the plasma concentration and no impact on blood pressure compared to liver-derived Agt.